Shape, size and topology effect investigation on 3D printed honeycomb structures - Mohamad Rizwan Bin Abdul Rahman (2016)
Honeycomb structures have applications in many engineering industries due to their desirable attributes in absorbing energy as well as to reduce material to volume ratio. The objective of this project is to establish the relationship between the in-plane honeycomb mechanical properties to the bulk material properties. The shape of the different structures are varied and the relative density were kept close to a constant of 20%. The mechanical properties of various shapes of honeycomb structures in the in-plane direction were analysed through Finite Element Modelling (FEM) and compression tests. FEM was simulated using ANSYS software whereas the compression test was conducted in accordance to ASTM standard C364 on an Instron 5569 Machine. The mechanism for failure in the elastic-plastic region was explored in terms of the local deformations observed. It was found that square-shaped cell structures have the highest elastic modulus and energy absorption values. Auxetic hourglass-shaped cell structure has the least energy absorption value. Future works were proposed to achieve a plausible continuation of the investigation.